Analysis of the Effect of Service Quality on User Satisfaction of McDonald's Application Using E-Servqual and Importance Performance Analysis (IPA) Methods - Indah Yansi Nofianto; Dwi Sukma Donoriyanto (Universitas KH. Abdul Chalim Mojokerto, 2025)
The rapid expansion of digital services has intensified competition in the online food delivery (OFD) industry, pushing businesses to enhance service quality to meet customer expectations. This study evaluates the McDonald's mobile application using the E-SERVQUAL model and Importance Performance Analysis (IPA) to examine the link between service quality dimensions and user satisfaction. A quantitative approach was used, with data collected from McDonald's app users in Indonesia through online questionnaires. The findings highlight that responsiveness, reliability, and system efficiency are critical factors affecting customer satisfaction, while application security, transaction smoothness, and system responsiveness require improvement. Based on the results, recommendations were proposed to enhance system stability, security features, and user interface design, ultimately aiming to increase customer satisfaction and loyalty in the competitive digital food service market.